Prevalence of postmastectomy pain syndrome and associated risk factors: A large single-institution cohort study - Gong, Youwei (Medicine (Baltimore), 2020)
Postmastectomy pain syndrome (PMPS) is a frequent complication of breast surgery, and is considered a chronic neuropathic pain in the side of surgery which persists more than 3 months. We conducted a retrospective analysis of the largest reported cohort to investigate the prevalence of PMPS and to analyze its associated risk factors as well as the influence on quality of life (QoL). Two thousand thirty-three surgically-treated female patients diagnosed between 2012 and 2017 with early-stage breast cancer were asked to complete a questionnaire survey about their current chronic neuropathic pain problems and quality of life. Multivariate logistic regression analyses were applied to determine the associated risk factors of PMPS. Results have shown that 1983 (97.5%) patients responded and completed a questionnaire survey. Among them, PMPS was found in 28.2% of patients. In univariate analysis, age≤35 years, tumor staging, history of chronic pain, total mastectomy, and axillary lymph node dissection (ALND) were significantly correlated with PMPS (P < .05). Multivariate analysis showed that age≤35 years, history of chronic pain, total mastectomy, and ALND were the independent risk factors of PMPS. QoL outcomes have shown that the global QoL score, physical function score, role function score, and social function score in the PMPS group were reduced in the PMPS group (P < .05), while the difference in emotional function score and cognitive function score showed no statistical significance (P > .05). Besides, patients with PMPS have worse body image, sexual enjoyment, and more breast symptoms. In conclusion, PMPS is linked with a high incidence among breast cancer patients, and has a considerable negative influence on the quality of life. In addition, age, total mastectomy, ALND, and history of chronic pain are the independent risk factors of PMPS.